Influence of Applying IFRS 17 on Financial Reports : An Exploratory Study of Iraqi Insurance Companies (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:           This research aims to identify deficiencies in the financial statements of insurance firms operating in Iraq concerning their adherence to the International Financial Reporting Standard IFRS 4. Additionally, it emphasizes the significance of implementing the IFRS 17 financial reporting standard in Iraqi insurance companies and its role in rectifying the deficiencies in financial reporting that arise from the application of IFRS 4. The primary objective of this study provides a comprehensive analysis of the effects that the implementation of the International Financial Reporting Standard (IFRS) 17 has on the financial statements of insurance companies operating in Iraq. The researchers employed a descriptive and analytical methodology, utilizing an empirical investigation of financial data released by insurance companies in Iraq. These companies constituted the sample for the study. In addition, a survey was administered to a total of 173 individuals who possess expertise in the subject matter. Out of these respondents, 154 completed the questionnaire, and the resulting data was subjected to analysis utilizing the statistical software SPSS. The findings of the study unveiled several noteworthy observations. These include a robust positive impact, which is both statistically significant and evident, of implementing the IFRS 17 standard on various aspects such as disclosure and presentation, financial reporting quality, financial statements, net income and retained earnings, as well as financial solvency within the Iraqi insurance sector. The findings of the study also indicated a robust and statistically significant correlation between the implementation of the IFRS 17 standard and enhancements in the quality of financial reporting, financial statement quality, net income, and retained earnings, as well as financial solvency within the Iraqi insurance sector.